y is increased by 6.
17
3/5 x 5/12 x 4/15 = 3 x 5 x 4/5 x 12 x 15= 5 x (3 x 4)/5 x 12 x 15= 1/15
let x be the number, then: (x + 1) × 2 + 5 = x + 1 → 2x + 2 + 5 = x + 1 → 2x + 7 = x + 1 → 2x - x = 1 - 7 → x = -6 The number is -6. Checking: -6 +1 = -5; 5 × 2 = -10; -10 + 5 = -5 which is the same as -6 + 1 = -5.
12
x + 12. If the unknown number is represented by x, the expression for a number increased by 12 would be x + 12.
When this question is interpreted to mean: Solve the following for x: (x+5)+12=7x Then the answer is: x=17/6 Or approximately 19.83333
y is increased by 6.
x + (-12) = 28 So x = 28 + 12 = 40
17
x/12 = 1/5 x = 12(1/5) x = 12/5 x = 2 2/5
12 x 5 = 60 That's because 12 x 100 = 600 12/2 = 6
3/5 x 5/12 x 4/15 = 3 x 5 x 4/5 x 12 x 15= 5 x (3 x 4)/5 x 12 x 15= 1/15
let x be the number, then: (x + 1) × 2 + 5 = x + 1 → 2x + 2 + 5 = x + 1 → 2x + 7 = x + 1 → 2x - x = 1 - 7 → x = -6 The number is -6. Checking: -6 +1 = -5; 5 × 2 = -10; -10 + 5 = -5 which is the same as -6 + 1 = -5.
X-5^2
12 x 12 x 12 x 12 x 12
let the denominator=x then numerator=3x Thus the fraction=3x/x now according to given condition if the numerator is decreased by 1 and denominator increased by 2 the new fraction would be 3x-1/x+2 which will be equal to 5/2 thus 3x-1/x+2=5/2 2(3x-1)=5(x+2) 6x-2=5x+10 x=12 thus the original fraction is 3(12)/12=36/12 Check:36-1/12+2=35/14=5/2:)